WALI HAKIM TERHADAP PERNIKAHAN ANAK DI LUAR NIKAH DALAM PERSPEKTIF PANDANGAN KEPALA KUA: (Studi Kasus KUA Kecamatan Diwek Kabupaten Jombang) - Siti Khotimah; Muhammad (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This research aims to explore the role of guardian judges in the process of resolving cases of child marriage out of wedlock, as well as to analyze the views of tthe Headd of tthe Diwek Religiouss Affairss Offices (KUA) regarding the actions taken in handling this problem. Thed researchd methodd usedd is dqualitative with a normative juridical approach. Data was collected through interviews, observation and documentation. The results of the research show that the views of the Head of KUA Diwek regarding the marriage of children out of wedlock are in accordance with legal provisions, such as PMA Number 30 of 2005 and KHI Articles 19-23. However, its implementation requires adjustments in administrative records to protect privacy and benefits and prevent negative impacts. The Head of KUA Diwek plays an active role in handling this case by dialogue with the parents involved to ensure legal recognition and provide understanding and education in accordance with applicable laws, both the Law and KHI..